AKTUALISASI-DIRI (SELF-ACTUALIZATION); SEBUAH MANIFESTASI PUNCAK POTENSI INDIVIDU BERKEPRIBADIAN SEHAT (Sebuah Konsep Teori Dinamika-Holistik Abraham Maslow) - Mohamat Hadori (LP2M Universitas Ibrahimy, 2015)
Self - actualization is the highest level in Holistic Dynamics theory to be achieved of an individual has already gets some basic requirements below. Maslow subsequently extended the idea to include his observations of humans' innate curiosity. His theories parallel many other theories of human developmental psychology, some of which focus on describing the stages of growth in humans. Maslow used the terms hierarchy of needs; physiological needs, safety needs, love and belonging needs, self - esteem needs ,self - actualization . Maslow also mentioned that a healthy person is a person able to actualize themselves well and draw , they can also pay attention to the needs of higher ie fulfill the potential they have and to know and understand the world around them.